Prevalence, antimicrobial susceptibility and characterization of Staphylococcus aureus and methicillin-resistant Staphylococcus aureus isolated from dairy industries in north-central and north-eastern Greece - Papadopoulos, Panagiotis; Papadopoulos, Theofilos; Angelidis, Apostolos S.; Kotzamanidis, Charalampos; Zdragas, Antonios; Papa, Anna; Filioussis, George; Sergelidis, Daniel (International journal of food microbiology, 2019)
Staphylococcus aureus is an important cause of food intoxication, whereas methicillin-resistant S. aureus (MRSA) constitutes a serious public-health concern due to its ability to colonize and infect humans and animals. S. aureus and MRSA have often been isolated from milk and dairy products. The objectives of this study were to estimate the prevalence and the antimicrobial resistance of S. aureus and MRSA in four Greek dairy industries, to identify virulence factors of MRSA isolates and to describe their genetic diversity, in order to identify possible epidemiological links and evaluate the risk of MRSA dissemination to the community. S. aureus was isolated from 67 out of 305 (22.0%) dairy industry samples (bulk-tank milk, dairy products, employee nasal swabs and equipment/surface swabs). Almost all (99%) of the 227 corresponding S. aureus isolates (approximately 4 isolates per positive sample) were resistant to at least one antimicrobial and 22% were multi-drug resistant (MDR). MRSA were isolated from 11 different samples (3.6%) originating from three of the dairy plants. All MRSA isolates were capable of forming biofilms, while staphylococcal enterotoxin (SE) genes were detected in 91% of the MRSA isolates, with sec being the most frequent. All of the MRSA isolates harbored the mecA gene but the mecC and Pandon-Valentine leucocidin (PVL) genes were not detected. Pulse-Field Gel Electrophoresis (PFGE) analysis showed genetic diversity among the MRSA isolates and indicated clonal circulation in one of the dairy plants. Seven spa types were identified among the MRSA isolates with the most prevalent (t065) isolated only in one dairy plant. Certain spa types (t065, t337 and t3536) were isolated for the first time in Greece. The presence of MDR, biofilm-forming and enterotoxigenic MRSA strains in dairy plant facilities may lead to their dissemination to the community, but also to staphylococcal food poisoning, when conditions are favorable. The study's findings highlight the need for continuous monitoring of the dairy production chain, the need for re-evaluating the implemented cleaning and sanitizing processes and the adoption of preventive strategies in order to minimize public-health risks. •Of 305 samples tested, 22.0% were S. aureus-positive & 3.6% were MRSA-positive.•Most MRSA isolates belonged to spa type t065.•spa types t065, t337 and t3536 were isolated for the first time in Greece.•Almost all MRSA isolates harbored SE-genes; sec being most frequent.•All MRSA isolates were capable to form biofilm.